ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN DAN KONTRIBUSI PEKERJA PEREMPUAN RUMAH TANGGA MISKIN DI KECAMATAN KARANGASEM - Meliana Ari Santi, Putu Indah; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The purpose of this study was to analyze the effect of age, education level, working hours and number of dependents on the income of women workers in poor households in Karangasem District, analyze the effect of age, education level, working hours, number of family dependents and income on contribution women workers in poor households in Karangasem District, and analyze whether age, education level, working hours and number of dependents have an indirect effect on the contribution through income of women workers. The data in this study used primary data which was taken as a sample of 123 female workers. The sampling method used is a non-probability sampling technique with the accidental sampling method uses path analysis techniques. The results showed that age, education level, working hours and number of dependents had a positive and significant effect on the income of female workers and age, education level, number of family dependents had a positive and significant impact on the contribution of female workers through income as an intervening variable while for the outpouring of working hours. positive but not significant effect on the contribution of women workers.